Historical account and current ecological knowledge of the southernmost lizard in the world, Liolaemus magellanicus (Squamata: Liolaemidae) - Fabian M. Jaksic (Revista Chilena de Historia Natural, 2022)
Abstract Background The systematics of Liolaemus magellanicus has been relatively well researched, but despite its recognition as the southernmost lizard in the world, scant attention has been paid to the discovery, distribution, biogeography, and ecology of this lizard at the southern tip of South America. I hereby research such aspects and collate the most relevant information reported in the primary literature. Methods and Results I conducted a selective review of the history of discovery, distributional records, biogeography, and ecological features of L. magellanicus, as recorded in mainstream journals and landmark monographs and books. I specifically omitted the work on the systematics of the species and genus because its complexity warrants separate treatment. I found scattered references to this lizard starting with the chronicles of several overseas expeditions (British, French, and Swedish), with Darwin, Jacquinot and Guichenot, and Anderson and Ohlin acting as informers; and culminating with Skottsberg, a traveler, and Bridges, an early settler in Tierra del Fuego Island. Modern treatment of this species started with Hellmich in the 1930s and Donoso-Barros in the 1960s in Chile, and with Cei in Argentina in the 1960s and has continued chiefly in the latter country until today. Discussion I propose this species as a model ectothermic vertebrate that may serve to test hypotheses about: (a) Resource allocation strategies to deal with a harsh environment that affords limited opportunities for foraging and reproductive activities of a lizard. (b) Behavioral strategies for dealing with thermoregulation, food, and mate acquisition, and care –if any—of offspring. (c) Its place within the rather impoverished food web of which this species forms part of. This relatively new species, which persisted in glacial refuges before being cut off into two subpopulations—one mainlander, another islander—also offers fertile ground for testing population genetic, evolutionary, and phylogeographic hypotheses. I think that biogeographers, systematists, evolutionists, physiologists, and ecologists should take advantage of this uniquely positioned species in the southernmost margin of the world.